KOMPETENSI PROFESIONAL GURU SD NEGERI 43 MANDAU KABUPATEN BENGKALIS - Susanti; Zufriady; Otang Kurniaman (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this research was to describe teachers’ professional competence at SD Negeri 43 Mandau Bengkalis. This research was conducted at SD Negeri 43 Mandau Bengkalis in September 2020. The type of this research was quantitative, which provided a description of the current condition of the research objects. The samples in this research were selected using a saturated sampling technique. The samples consisted of all teachers at SD Negeri 43 Mandau Bengkalis, totaling 16 teachers. Data were collected through a questionnaire distributed via Google Form containing statements about teachers’ professional competence with four alternative answers across 57 questions. The research results concluded that teachers’ professional competence at SD Negeri 43 Mandau Bengkalis reached 80.91% and was categorized as “Good.” The number of core competencies scoring in the interval of 85–100 with the category “Very Good” was one core competency, those in the interval of 70–84 with the category “Good” were two core competencies, those in the interval of 50–69 with the category “Enough” was one core competency, and those in the interval of 0–49 with the category “Less” was zero core competencies.